Health and citizenship - Rachid Bydlowski, Cynthia (O Mundo da Saúde, 2007)
Brazilian population health reflects the huge structural problems the country must deal with. There is a very close relationship between health and life conditions, as is pointed out by several authors. In the present work this relationship is discussed. The exercise of citizenship is described as the strategy to be used for solving this awful situation currently experienced by the Brazilian population. A Health Promotion process is also proposed. For the exercise of citizenship to be effective we consider essential to have a consistent educational process, targeted mainly to junior and high school students. This educational process should be focused not only on professional training but also at on education for citizenship.